Comparing CST Lesion Metrics as Biomarkers for Recovery of Motor and Proprioceptive Impairments After Stroke. (October 2019) - Findlater, Sonja E.; Hawe, Rachel L.; Mazerolle, Erin L.; Al Sultan, Abdulaziz S.; Cassidy, Jessica M.; Scott, Stephen H.; Pike, G. Bruce; Dukelow, Sean P.
Background. Corticospinal tract (CST) damage is considered a biomarker for stroke recovery. Several methods have been used to define CST damage and examine its relationship to motor performance, but which method is most useful remains unclear. Proprioceptive impairment also affects stroke recovery and may be related to CST damage. Methods. Robotic assessment quantified upper-limb motor and proprioceptive performance at 2 weeks and 6 months poststroke (n = 149). Three previously-established CST lesion metrics were calculated using clinical neuroimaging. Diffusion magnetic resonance imaging quantified CST microstructure in a subset of participants (n = 21). Statistical region of interest (sROI) analysis identified lesion locations associated with motor and proprioceptive deficits. Results. CST lesion metrics were moderately correlated with motor scores at 2 weeks and 6 months poststroke. CST fractional anisotropy (FA) was correlated with motor scores at 1 month poststroke, but not at 6 months. The FA ratio of the posterior limb of the internal capsule was not correlated with motor performance. CST lesion metrics were moderately correlated with proprioceptive scores at 2 weeks and 6 months poststroke. sROI analysis confirmed that CST damage was associated with motor and proprioceptive deficits and additionally found that putamen, internal capsule, and corticopontocerebellar tract lesions were associated with poor motor performance. Conclusions. Across all methods used to quantify CST damage, correlations with motor or proprioceptive performance were moderate at best. Future research is needed to identify complementary or alternative biomarkers to address the complexity and heterogeneity of stroke recovery.